Pengaruh Harga, Kepercayaan dan Citra Perusahaan Terhadap Loyalitas Pelanggan Perusahaan Otobus Kurnia (PO. Kurnia) Rute Padang-Medan - Fera Mardiana; Rose Rahmidani (Jurnal Ecogen, 2020)
This study aims to determine the effect of price, trust and corporate image on customer loyalty of the Kurnia otobus (PO. Kurnia) company in the Padang-Medan route. This type of research is causative. The population in this study were all PO service users (passengers). Kurnia Padang-Medan route. Samples were taken using the Slovin formula with 100 respondents and selected by purposive sampling technique. The type of data used in this study is primary data obtained through distributing questionnaires to Kurnia bus passengers with predetermined criteria. The analytical method used is multiple regression analysis using SPSS version 20. The results of this study indicate that: (1) price, trust, company image have a positive and significant effect on customer loyalty (2) price has a positive and significant effect on customer loyalty (3) trust positive and significant effect on customer loyalty (4) company image positive and significant effect on customer loyalty.Keywords: price, trust, corporate image, customer loyalty